Thin carbon hollow fiber membrane with Knudsen diffusion for hydrogen/alkane separation: Effects of hollow fiber module design and gas flow mode. (4th March 2020) - Wey, Ming-Yen; Chen, Hsish-Han; Lin, Yu-Ting; Tseng, Hui-Hsin
Abstract: Recovery of heavier hydrocarbons, C2 ~C4 olefins and paraffins, from gas streams is of great importance economically. In this study, asymmetric carbon hollow fiber membranes (CHFMs) were prepared by a one-step vacuum-assisted dip coating and pyrolysis, and investigated for H2 /CO2, H2 /C2 H6, and H2 /C3 H8 separations. To increase the mechanical strength of the CHFMs, a porous alumina hollow fiber with ID/OD = 2 mm/4 mm was used as the supporting material. A solution of polyetherimide in N-methyl-2-pyrrolidone was used as the casting solution. The effects of (1) membrane preparation parameters, (2) fiber packing densities, (3) fiber packing arrangement, and (4) gas flow configuration (inside-out or outside-in) on the gas-separation performance were also investigated. The results showed that decreasing the concentration of the casting dope and the number of coating cycles was found to be the most effective approach to increase the H2 permeance, while maintaining the H2 /CO2 selectivity. Further, as the fiber packing density was increased from 5.54% to 38.78% for the hexagonal packing configuration, the H2 permeance increased from 362.04 GPU to 711.61 GPU, without any decrease in the gas selectivity. The as-prepared CHFM exhibited the maximum gas permeance of 711.61 GPU for H2 and the following gas selectivity: 2.79, 4.65, and 5.34 towards H2 /CO2, H2 /C2 H6, and H2 /C3 H8, respectively. The successful preparation and modularization of the CHFM is advantageous and industrially relevant for several gas-separation applications, such as H2 energy production from CO2, C2 H6, and C3 H8, and olefins/paraffins recovery. Graphical abstract: Image 1 Highlights: Thin carbon hollow fiber membrane preparation and potential in industry application. The pore size was shrunk by vacuum application after withdrawing step. The carbon hollow fiber membrane exhibited good perm-selectivity towards H2 /alkane. The effects of hollow fiber module design and gas flow mode were evaluated.